COMPARISON BETWEEN BELUNTAS (PLUCHEA INDICA LEES) FRACTION AND KETOCONAZOLE INVITRO ON CANDIDA ALBICANS - Marsasi, Bina; Yuwono, Yuwono; Salni, Salni (Fakultas Kedokteran Universitas Sriwijaya, 2019)
Beluntas leaves are useful as a treatment for flour albus and discharge caused by fungi. This study aims to find the anti-fungal activity of fraction of beluntas (Pluchea indica Lees) leaf extract against Candida albicans. This research is an in vitro experimental study using the Posttest-only Control Group Design study design. Methanol extract is obtained through maceration process while the fraction is through liquid-liquid fractionation. The most active fraction is determined by the antifungal activity test. The most active fractions with concentrations of 10%, 5%, 2.5%, 1.25%, 0.625% and the diameter of the inhibition zone 0.3125% were measured by the liquid dilution method. Equivalence with drugs is assessed through regression analysis, then the class of active compounds is determined through bioautographic testing using thin layer chromatography. The research results obtained methanol-fraction-water can inhibit the growth of Candida albicans while the methanol extract, n-hexane and ethyl acetate do not inhibit. The methanol fraction of water which has inhibition zone diameters starts at a concentration of 0.3125% with an average diameter of 7.34 mm and at a concentration of 10% the largest diameter of 17.10 mm is obtained. Through the diluent liquid and the KHM solid fraction from the methanol-water fraction is inhibited at a concentration of 0.3125%. Equivalence test shows that 1 mg / ml of ketoconazole is equivalent to 39,561 mg / ml of methanol-water fraction of beluntas leaves. Compounds that inhibit fungi are thought to be active groups of flavonoid and alkaloid compounds. The methanol-water fraction of beluntas leaves (Pluchea indica Lees) has antifungal activity against Candida albicans in vitro.